2018
DOI: 10.1149/2.0721813jes
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Iron-Based Fuel Cell Catalysts by Non-Catalytic Platinum

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…53,54 The present hybrid Pt/FeNC catalysts are therefore promising for application at the cathode of DMFC, being tolerant to methanol crossover from the anode to the cathode and much more durable than FeNC alone, as previously shown in PEMFC. 46 The effect of cell temperature was first investigated, highlighting strong improvement from 80 to 100°C (Figure 1b). The cell performance obtained with Pt 1.0 Fe 1.0 d and Pt 2.0 Fe 1.0 d is comparable, the difference lying within the reproducibility error.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…53,54 The present hybrid Pt/FeNC catalysts are therefore promising for application at the cathode of DMFC, being tolerant to methanol crossover from the anode to the cathode and much more durable than FeNC alone, as previously shown in PEMFC. 46 The effect of cell temperature was first investigated, highlighting strong improvement from 80 to 100°C (Figure 1b). The cell performance obtained with Pt 1.0 Fe 1.0 d and Pt 2.0 Fe 1.0 d is comparable, the difference lying within the reproducibility error.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the cell performance at high voltage (kinetically controlled region) is very similar for both cathode catalysts, as expected from our previous work. 46 Since the content of 1 wt % Pt was shown in PEMFC to be the lower-end limit for complete durability over at least 50 h in PEMFC, 46 we then focused the DMFC measurements on the Pt 2.0 Fe 1.0 d cathode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While significantly more durable than NH 3 -pyrolyzed catalysts, they also suffer from a slow but steady linear decline with duration of operation in PEMFC. 26,29 Two main degradation mechanisms of such materials have been identified: (1) irreversible iron leaching from Fe particles imperfectly embedded in carbon or from FeN 4 active sites; 30 and (2) reversible degradation induced by the hydrogen peroxide by-product formed during ORR in acidic medium; 31,32 Mechanism (1) was investigated with online mass-spectrometry and revealed that Fe leaching resulted from carbon corrosion during startup/shutdown AST, while Fe leaching during load-cycling AST mainly originated from Fe particles imperfectly surrounded by a N-C layer. The FeN 4 moieties were mostly stable during load-cycling AST in inert-gas saturated acidic medium, in a broad range of temperature and up to 10,000 cycles.…”
mentioning
confidence: 99%